The Genetic Adjuvants Interleukin-12 and Granulocyte-Macrophage Colony Stimulating Factor Enhance the Immunogenicity of an Ebola Virus Deoxyribonucleic Acid Vaccine in Mice. (19th July 2018) - Suschak, John J; Bagley, Kenneth; Shoemaker, Charles J; Six, Carolyn; Kwilas, Steven; Dupuy, Lesley C; Schmaljohn, Connie S
Abstract: In previous studies, we showed that deoxyribonucleic acid (DNA) vaccines expressing codon-optimized filovirus envelope glycoprotein genes protect mice and nonhuman primates from viral challenge when delivered by intramuscular (IM) electroporation (EP). To determine whether we could achieve equivalent immunogenicity and protective efficacy by a simplified delivery method, we generated DNA vaccine plasmids expressing genetic adjuvants to potentiate immune responses. We tested the Th 1-inducing cytokine interleukin-12 and the granulocyte growth factor granulocyte-macrophage colony stimulating factor, both of which have demonstrated significant adjuvant effect when included in clinical DNA vaccine formulations. In addition, because interferon (IFN)-αβ is required for DNA vaccine-induced immunity, we tested inclusion of a potent stimulator of the IFN-αβ pathway. Our data suggest that IM vaccination of mice with plasmid DNA encoding genetic adjuvants enhances vaccine immunogenicity, resulting in increased anti-Ebola virus (EBOV) immunoglobulin G and T-cell responses. Codelivery of genetic adjuvants also improved EBOV neutralizing capability compared with vaccine alone. Finally, IM vaccination with plasmid EBOV and genetic adjuvants provided complete protection against EBOV challenge. Overall, our data suggest that codelivery of genetic adjuvants with filovirus DNA vaccines using IM delivery can provide comparable efficacy to the same DNA vaccines when delivered using IM-EP devices.